Physicochemical And Morphological Characterisation Studies Of Fabrics Treated With Lavender Essential Oil-Based Nanoemulsion - Azlan bin Kamari, Norjan binti Yusof (Tanjung Malim, 2024)
Physicochemical And Morphological Characterisation Studies Of Fabrics Treated With Lavender Essential Oil-Based Nanoemulsion by Azlan bin Kamari, Norjan binti Yusof